Pelatihan Komunikasi Interpersonal bagi Mahasiswa PGMI UIN Mahmud Yunus Batusangkar dalam Rangka Meningkatkan Kompetensi Profesional Calon Guru - Risa Amalia; Rudi Rahman; Thatalia Yunda (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Interpersonal communication is one of the essential skills that prospective teachers must have, especially in building positive relationships with students, parents, and colleagues. Students of the PGMI Study Program at UIN Mahmud Yunus Batusangkar, as prospective professional teachers, are required not only to master teaching materials but also to have the ability to communicate effectively, empathetically, and provide solutions in various educational contexts. However, based on initial observations and the results of group discussions, it was found that many PGMI students still experience difficulties in expressing ideas, building two-way communication, and conveying messages persuasively and constructively in academic environments and teaching practice. The objectives of this activity are: (1) to increase students' understanding of the concept and importance of interpersonal communication in the teaching profession; (2) to train communication skills that support a humanistic and dialogical learning process; and (3) to shape the character of prospective teachers who are communicative, empathetic, and professional. The training method uses Participatory Action Research (PAR) using a pre-test and post-test measurement system. This training program is designed to strengthen interpersonal communication skills for PGMI students through interactive and practical approaches, such as learning simulations, case studies, role-plays, and reflective discussions. The results of this service are an increase in students' interpersonal communication skills, where before the training, the score was 58.8% in the sufficient category; after being given interpersonal communication training, the students experienced an increase to 88% in the very good category.